RESEARCH OF STRUCTURE AND PROPERTIES OF PROTEINS OF LOCAL VARIETIES OF LENTIL GRAIN (American Journal of Interdisciplinary Research and Development, 2022)
Physical-chemical and functional properties of the protein isolate from lentil grains have been determined. The conformational structure of protein molecules has been determined by IR spectroscopy. It has been established that protein isolates retain their native state during deep processing.